Feminicidio. De la teoría feminista al Derecho Penal Peruano - Rodríguez Vásquez, Julio Alberto (Pontificia Universidad Católica del Perú, 2023)
This article addresses the evolution of the category of femicide. It studies its birth in feminist theory, its translation and development in Latin American academia, its use in international law and its transformation into a crime. The analysis of the evolution of this concept allows highlighting its singular and autonomous character. Thus, the study of this category helps to strengthen the doctrine that defines femicide as the killing of a woman for gender reasons, that is, the killing of a woman in a context in which the victim failed to comply with gender stereotypes.

El presente artículo aborda la evolución de la categoría feminicidio. Se estudia su nacimiento en la teoría feminista, su traducción y desarrollo en la academia latinoamericana, su empleo en el Derecho Internacional y su transformación en un delito. El análisis de la evolución de este concepto permite destacar su carácter singular y autónomo. Así, el estudio de esta categoría ayuda a afianzar la doctrina que define al feminicidio como el matar a una mujer por razones de género, esto es, matar a una mujer en un contexto en el que la víctima incumplió con los estereotipos de género.
Femicide. From feminist theory to peruvian criminal law
Keywords: Femicide; Criminal Law; Gender; Legal Feminism; Patriarchy; Discrimination; Feminicidio; Derecho Penal; Género; Feminismo Jurídico; Patriarcado; Discriminación; https://purl.org/pe-repo/ocde/ford#5.05.00